Identifying unmet informational needs in the inpatient setting to increase patient and caregiver engagement in the context of pediatric hematopoietic stem cell transplantation. (28th October 2015) - Kaziunas, Elizabeth; Hanauer, David A; Ackerman, Mark S; Choi, Sung Won
Abstract: Background Patient-centered care has been shown to improve patient outcomes, satisfaction, and engagement. However, there is a paucity of research on patient-centered care in the inpatient setting, including an understanding of unmet informational needs that may be limiting patient engagement. Pediatric hematopoietic stem cell transplantation (HSCT) represents an ideal patient population for elucidating unmet informational needs, due to the procedure's complexity and its requirement for caregiver involvement. Methods We conducted field observations and semi-structured interviews of pediatric HSCT caregivers and patients to identify informational challenges in the inpatient hospital setting. Data were analyzed using a thematic grounded theory approach. Results Three stages of the caregiving experience that could potentially be supported by a health information technology system, with the goal of enhancing patient/caregiver engagement, were identified: (1) navigating the health system and learning to communicate effectively with the healthcare team, (2) managing daily challenges of caregiving, and (3) transitioning from inpatient care to long-term outpatient management. Discussion We provide four practical recommendations to meet the informational needs of pediatric HSCT patients and caregivers: (1) provide patients/caregivers with real-time access to electronic health record data, (2) provide information about the clinical trials in which the patient is enrolled, (3) provide information about the patient's care team, and (4) properly prepare patients and caregivers for hospital discharge. Conclusion Pediatric HSCT caregivers and patients have multiple informational needs that could be met with a health information technology system that integrates data from several sources, including electronic health records. Meeting these needs could reduce patients' and caregivers' anxiety surrounding the care process; reduce information asymmetry between caregivers/patients and providers; empower patients/caregivers to participate in the care process; and, ultimately, increase patient/caregiver engagement in the care process.